Membangun Masyarakat Berpengharapan: Belajar dari Pengalaman Masyarakat Dusun Caben Kabupaten Bantul - Agus Tridiatno Yoachim; Chatarina Suryanti (Religió: Jurnal Studi Agama-agama, 2020)
This paper describes how the people of Caben, Bantul, Yogyakarta, were able to carry out the crisis of earthquake on May 27, 2006. It happened because of their hopes and submission to God. These attitudes have been refined through spreading love and solidarity between people. This research found that love and solidarity cannot be separated from the virtue of hope and faith. These two essential virtues are very important for those who suffer from a disaster. Learning from the people of Caben, Bantul, this paper considers that a hopeful community could be constructed by spreading love and solidary. Social encounters and cooperation must be continuously preserved to make social cohesion and network. It represents a thankful behavior toward the mercy of God. It is always relevant to have such a hopeful community here in Indonesia as the country of disaster.